Experimental simulation and fuzzy modelling of landfill biogas production from low-biodegradable MBT waste under leachate recirculation. Issue 20 (18th October 2018) - Di Addario, Martina; Ruggeri, Bernardo
ABSTRACT: In the perspective of a sustainable waste management, biodegradable waste destined to landfilling should be reduced. This work aims to study a combination of waste pretreatments and leachate recirculation. A lab-scale experiment and fuzzy-modelling were chosen to predict cumulative methane production from low-biodegradable waste (LBW) under leachate recirculation. Thanks to moisture increase, the degradation of LBW was reactivated and the cumulative methane production reached 28 NL CH4 kg −1 after 442 days. The organic fraction was stabilized with a final chemical oxygen demand (COD) of 81 mg L −1 . Fuzzy model was proposed as an alternative to the common deterministic models, affected by high uncertainties. Eleven inputs (pH, Redox potential, COD, volatile fatty acids, ammonium content, age, temperature, moisture content, organic fraction concentration, particle size and recirculation flow rate) were identified as antecedent, and two outputs, or consequents, were chosen: methane production rate and methane fraction in biogas. Antecedents and consequents were linked by 84 IF–THEN rules in a linguistic form. The model was also tested on six literature studies chosen to test different operational conditions and waste qualities. The model outputs fitted the experimental data reasonably well, confirming the potential use of fuzzy macro-approach to model sustainable landfilling.